Response of Anguilla bicolor Glass Eel to Different Light Colors - Riyanto, Mochammad; Aminah, Ai Siti; Mawardi, Wazir; Wahju, Ronny Irawan (Journal Omni-Akuatika, 2023)
The response of eel fish (Anguilla bicolor) glass eel stadia to different light is fundamental knowledge for developing fishing methods and conserving fish resources. The study aimed to describe how glass eel fish react to different types of light. In the laboratory, glass eels were observed responding to red, blue, and white LED light versus no light as controls. Glass eels ranging in size from 4.0 to 6.1 cm and weighing up to 0.28 g were caught in the Pelabuhanratu estuary of the Cimandiri River. Observations were made for 31 days, beginning five days after the glass eel was captured. The Mann Whitney and Kruskal-Wallis tests were used to describe differences of the glass eel's response to light. Observations showed that glass eels responded more to dark zones with values above 80% when compared to zones given red, blue, and white LED light. The percentage of fish in red LED lights was 23±0.22% higher, with the number of fish on blue LED lights by 10±0.21% and white LED lights 8±0.15% (p<0.05, Kruskal-Wallis). The difference in response to light can be used for glass eel catching applications, especially lamps for eel fish aids and eel conservation to create fishing zones and eels.Keywords: Anguilla bicolor, eel behavior, glass eel, LED light, response to light